Between performance and fragility: Constructions of masculinity in high school boys’ discourses on gender - Hakeem, Hasheem (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2024)
This article presents the results of a qualitative case study of high school boys’ perceptions of gender diversity. Data were collected by means of a questionnaire, audio recordings of discussions of two comics by trans writer Sophie Labelle, reflective journals, and semi-structured individual interviews. Three findings emerged from the data analysis: (1) support for biological and binary conceptions of gender; (2) cisgender fragility, that is, defensiveness when cisgender worldviews are challenged; and (3) the social performance of transphobia as a means of constructing hegemonic masculinity. We conclude with a discussion of the findings and their pedagogical implications.